Religionspedagogik - ett forskningsfält i tiden (Nordic Journal of Practical Theology, 2020)
The aim with the article is twofold: first to present religious education in a Nordic but foremost Swedish context, second to argue for a broad understanding of the research field. Through the examples given in the article the author argue that religious education give space for reflections about teaching and learning about/of/in religious phenomena, themes and other expressions of meaning-making and the conditions for them all in religious but also non-religious settings.The article presents a historic background to the emergence of religious education in a Nordic context. Thereafter research will be presented as representing four different but relating themes: content, performer, aim and method.It is argued that religious education is a research field that contributes to a deeper reflection on the opportunities and challenges that can be seen in relation to learning in religious environments and in relation to religious, and existential themes. Religious education contributes to a deeper understanding of the meaning-making that all people share and it is therefore a topic that finds great relevance and a clear justification in our time and in a globalized world.